A case of syncope and ventricular asystole triggered by postoperative nausea and vomiting. Issue 2 (26th November 2015) - Sakai, Michihiro; Terahata, Akihiro; Goto, Takahisa; Kaneko, Mitsuhisa
Summary: A 67‐year‐old, otherwise healthy female, developed recurrent syncope and ventricular asystole immediately after an uncomplicated total knee arthroplasty. The syncope was preceded by postoperative nausea and vomiting. The ECG findings during these episodes revealed high‐degree atrioventricular block followed by ventricular pauses, making it impossible to rule out a serious atrioventricular conduction abnormality. Further electrophysiological evaluation revealed that the cardiac conducting system was normal. Vagal dependence could not be confirmed; however a hypersensitive vagal response to postoperative nausea and vomiting appeared to be the most likely explanation.